On extensions of linear functionals with applications to non-symmetrically singular perturbations - Dudkin, M. E.; Vdovenko, T. (Methods of Functional Analysis and Topology, 2018)
The article is devoted to extensions of linear functionals, generated by scalar products, in a scale of Hilbert spaces. Such extensions are used to consider non-symmetrically singular rank one perturbations of H_-2-class. For comparison, we give main definitions and descriptions of singular non-symmetric perturbations of H_-1 and H_-2-classes.